Levels of high-sensitive troponin T and mid-regional pro-adrenomedullin after COVID-19 vaccination in vulnerable groups: monitoring cardiovascular safety of COVID-19 vaccination - Pudasaini, Samipa; Le, Ngoc Han; Huscher, Dörte; Holert, Fabian; Hillus, David; Tober-Lau, Pinkus; Kurth, Florian; Sander, Leif Erik; Möckel, Martin (Frontiers in Cardiovascular Medicine, 2024)
Background COVID-19 vaccines are well tolerated and effective but may have adverse effects on the cardiovascular system. Vaccine-associated myocardial injury was analysed by measuring high-sensitive troponin T (hsTnT); mid-regional pro-adrenomedullin (MR-proADM) levels were evaluated to assess endothelial dysfunction. Methods This was a prospective study with a vulnerable population of healthcare workers (HCWs) and elderly patients (>70 years) who were vaccinated with either one dose of ChAdOx1 nCov-19 adenoviral vector vaccine (AZ) followed by one dose of the BNT162b2 messenger RNA vaccine (BNT), or with two doses of BNT (12th of January - 30th of November 2021). HsTnT and MR-proADM were measured in blood samples at three visits (V1: 1st immediately before vaccination; V2, 3: 3–4 weeks after 1st and 2nd vaccination). HsTnT of HCWs was compared to a healthy reference population. Results N = 162 volunteers were included (V1 = 161; V2, V3 = 162 each). N = 74 (45.7%) received AZ/BNT and n = 88 (54.3%) received BNT/BNT [elderly: n = 20 (12.3%), HCWs: n = 68 (42.0%)]. Median hsTnT levels were 4 ng/L, 5 ng/L and 4 ng/L (V1-V3) for AZ/BNT and at 5 ng/L, 6 ng/L and 6 ng/L (V1-V3) for BNT/BNT. Compared to the reference population (n = 300), hsTnT was significantly higher at all visits for both vaccination groups (p < 0.01), without differences between the AZ/BNT and BNT/BNT cohort. Median MR-proADM values were 0.43 nmol/L, 0.45 nmol/L, 0.44 nmol/L (V1-V3) in the AZ/BNT cohort and 0.49 nmol/L, 0.44 nmol/L, 0.47 nmol/L for BNT/BNT, respectively. Change of median hsTnT and MR-proADM between visits did not show significant increases. One HCW experienced a permanent and three a transient hsTnT increase ≥14 ng/L. Conclusion No overall subtle, persistent cardiovascular involvement was observed after the 2nd COVID-19 vaccination. Elevated cardiovascular biomarkers in clinically asymptomatic individuals need further investigations.